2007
DOI: 10.1007/s10549-007-9597-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of manganese superoxide dismutase on growth and invasive properties of human estrogen-independent breast cancer cells

Abstract: Manganese superoxide dismutase (MnSOD) is known to play a role in cancer. MnSOD exerts a tumor suppressive effect in estrogen-dependent human breast cancer cells. In the present study we investigated the in vitro role of MnSOD in the growth of some aggressive and highly metastatic estrogen-independent breast cancer cells, i.e., MDA-MB231 and SKBR3 cells. We show that estrogen-independent cells expressed a significantly higher basal MnSOD level compared to estrogen-dependent human breast cancer cell lines (MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
92
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 43 publications
14
92
3
Order By: Relevance
“…MnSOD may also function as a tumor suppressor; for example, it may reduce growth of tumors associated with melanoma (2), pancreatic adenocarcinoma (3,4), colorectal cancer (5), ovarian cancer (6), breast cancer (7), and multiple myeloma (8). Conversely, MnSOD may promote tumor progression in cancers, such as fibrosarcoma (9), gastric cancer (10,11), glioblastoma (12), T-cell lymphoma (13), breast cancer (14,15), cervical cancer (16), prostate cancer (17), and lung cancer (18). Therefore, the precise role of MnSOD in tumorigenesis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…MnSOD may also function as a tumor suppressor; for example, it may reduce growth of tumors associated with melanoma (2), pancreatic adenocarcinoma (3,4), colorectal cancer (5), ovarian cancer (6), breast cancer (7), and multiple myeloma (8). Conversely, MnSOD may promote tumor progression in cancers, such as fibrosarcoma (9), gastric cancer (10,11), glioblastoma (12), T-cell lymphoma (13), breast cancer (14,15), cervical cancer (16), prostate cancer (17), and lung cancer (18). Therefore, the precise role of MnSOD in tumorigenesis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, oxidative stress is the result of what aerobic life greatly depends on oxidation. While aerobic cells enjoy this energy-producing reaction, they need to fight its harmful products at the same time [1]. To do so, organisms apply compound systems of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes such as CAT and SOD are antioxidants essentially required for cells' self-protection. They are key players in several reactions which prevent and treat the harms of oxidative stress [1]. The members of the SOD family dismutate su- shows the quantified data, as mean ± SD, through densitometric analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (2007) suggested that SOD can act as a tumor suppressor by decreasing growth and survival of breast cancer cells. On the other hand, some studies have reported a correlation between high SOD level and invasiveness of breast cancer (Tsanou et al, 2004;Kattan et al, 2008). Er et al (2004) speculated that upregulation of SOD expression induced by oxidative stress or local inflammation may contribute a selective growth advantage to tumor cells compared to their normal counterparts (Khan et al, 2010).…”
Section: Genes Expression In Human Breast Cancer Samplesmentioning
confidence: 99%